Assessment of size of adenoid-comparison of adenoidal nasopharyngeal ratio and nasal endoscopy in children with chronic adenoiditis - Hamza, Sunaina Binth; V. T., Ranjith (International Journal of Research in Medical Sciences, 2019)
Background: Adenoid hypertrophy (AH) is a common cause of upper airway obstruction in paediatric patients and can have a significant influence on the health of the child. Children who have hypertrophic adenoids often exhibit nasal obstruction, snoring, sleep apnea, otitis media with effusion and craniofacial abnormalities. The main objective of this study was to know the association between size of adenoids and occurrence of otitis media with effusion (OME) and to correlate the grades of AH by lateral nasopharyngeal radiograph and nasal endoscope. Methods: This was an observational cross-sectional study of 100 children who were diagnosed as chronic adenoiditis were studied clinically with relevant investigations. The digital X-ray nasopharynx lateral view and nasal endoscopic results of all the patients were analyzed and graded. Results: Mean Adenoidal-nasopharyngeal ratio for which OME was present was 0.72 which corresponds to X-ray grade 2. It was also found that 80.6% of X-ray grade 3 adenoids had OME and 100% of cases of endoscopic grade 4 adenoids had OME in either or both ears. 36 cases with grade 3 X-rays, 69% were in endoscopic grade 3 and 19.4% cases were shown to have complete choanal obstruction (grade 4). Conclusions: There is significant association between the size of adenoids and OME. The X-ray nasopharynx provides a more convenient method and nasal endoscopy is the gold standard method for determining whether the AH is clinically significant or not.